Human mesenchymal stem cell derived from bone marrow and umbilical cord display anti-cancer activity in cancer cell lines in vitro - Noor Atiqah Fakharuzi,; Moon, Nian Lim; Zuhairi Abdul Rahman,; Nurul Ain Nasim Mohd Yusof,; Ezalia Esa,; Kamal Shaik Fakiruddin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The anti-tumour efficacy of engineered mesenchymal stem cell (MSCs) in cancers have been well documented by several reports. However, the impact of MSCs on the pathogenesis of solid cancers remains elusive. The study aims to elucidate the role of MSCs from bone marrow (BMMSCs) and umbilical cord (UCMSCs) on the proliferation, apoptosis and clonogenicity of cancer cell including H2170 (squamous cell carcinoma), LN18 (glioblastoma) and MCF7 (breast cancer) in vitro. Highest concentration of conditioned medium derived from the UCMSCs was significantly (p<0.001) effective to inhibit the proliferation of H2170 (25.8 ± 3.5%), LN18 (17.6 ± 6.5%) and MCF7 (33.2 ± 6.8%) as compared to 100% viability in basal. Both MSCs and its conditioned medium were able to significantly (p<0.001) induce apoptosis (early and late) to the H2170 and LN18 cells. However, for MCF7 cells, co-cultured with both MSCs had higher impact on the apoptosis as compared to their condition medium. Furthermore, conditioned medium from UCMSCs were able to significantly reduced the number of colonies in H2170 (609.5 ± 4.9) and LN18 (171.3 ± 12.6) as compared to control (H2170; 1196.3 ±12.8 and LN18; 253.3 ± 12.3), suggesting that these two cancer cells are sensitive to the MSCs. Notably, by co-culturing of all three cancer cell lines with the MSCs’ conditioned medium, we found that there was an increased expression of more than two-fold in BAX, BAD, and APAF1 genes showing the ability of MSCs’ conditioned medium to induce the intrinsic apoptosis pathway in the cancer cells. Collectively, our findings demonstrated that the MSCs could induce apoptosis and inhibit both H2170 and LN18 cancer cell proliferation. Furthermore, this study did not find evidence of MSCs in enhancing tumorigenic characteristics of these cancer cells, and thus we postulate that MSCs are basically safe as a cell-based therapy in cancer treatment.